Fetal surgery for open spina bifida. (27th September 2019) - Sacco, Adalina; Ushakov, Fred; Thompson, Dominic; Peebles, Donald; Pandya, Pranav; De Coppi, Paolo; Wimalasundera, Ruwan; Attilakos, George; David, Anna Louise; Deprest, Jan
Abstract : Key content: Spina bifida is a congenital neurological condition with lifelong physical and mental effects. Open fetal repair of the spinal lesion has been shown to improve hindbrain herniation, ventriculoperitoneal shunting, independent mobility and bladder outcomes for the child and, despite an increased risk of prematurity, does not seem to increase the risk of neurodevelopmental impairment. Open fetal surgery is associated with maternal morbidity. Surgery at our institution is offered and performed according to internationally agreed criteria and protocols. Further evidence regarding long‐term outcomes, fetoscopic repair and alternative techniques is awaited. Learning objectives: To understand the clinical effects, potential prevention and prenatal diagnosis of spina bifida. To understand the rationale and evidence supporting the benefits and risks of fetal repair of open spina bifida. To understand the criteria defining those who are likely to benefit from fetal surgery. Ethical issues: The concept of the fetus as a patient, and issues surrounding fetal death or the need for resuscitation during fetal surgery. The associated maternal morbidity in a procedure performed solely for the benefit of the fetus/child. The financial implications of new surgical treatments.